Development of catalyst complexes for upgrading biomass into ester-based biolubricants for automotive applications: a review - Hossain, Md Anwar; Mohamed Iqbal, Mohammad Anwar; Julkapli, Nurhidayatullaili Muhd; Kong, Pei San; Juan, Joon Ching; Lee, Hwei Voon (Royal Society of Chemistry, 2018)
Biomass-derived oils are recognised as the most promising renewable resources for the production of ester-based biolubricants due to their biodegradable, non-toxic and metal adhering properties. Homogeneous acid catalysts have been conventionally used in catalytic esterification and transesterification for the synthesis of ester-based biolubricants. Although homogeneous acid catalysts encounter difficulty during phase separation, they exhibit superior selectivity and good stereochemistry and regiochemistry control in the reaction. Consequently, transition metal complex catalysts (also known as homogeneous organometallic catalysts) are proposed for biolubricant synthesis in order to achieve a higher selectivity and conversion. Herein, the potential of both homogeneous transition metal complexes and heterogeneous supported metal complexes towards the synthesis of biolubricants, particularly, in esterification and transesterification, as well as the upgrading process, including hydrogenation and in situ hydrogenation-esterification, is critically reviewed.